The biological basis and function of GNAS mutation in pseudomyxoma peritonei: a review - Lin, Yu-Lin; Ma, Ru; Li, Yan (Journal of cancer research and clinical oncology, 2020)
Purpose Pseudomyxoma peritonei (PMP) is a rare clinical malignancy syndrome characterized by the uncontrollable accumulation of copious mucinous ascites in the peritoneal cavity, resulting in “jelly belly”. The mechanism of tumor progression and mucin hypersecretion remains largely unknown, but GNAS mutation is a promising contributor. This review is to systemically summarize the biological background and variant features of GNAS , as well as the impacts of GNAS mutations on mucin expression, tumor cell proliferation, clinical-pathological characteristics, and prognosis of PMP. Methods NCBI PubMed database (in English) and WAN FANG DATA (in Chinese) were used for literature search. And NCBI Gene and Protein databases, Ensembl Genome Browser, COSMIC, UniProt, and RCSB PDB database were used for gene and protein review. Results GNAS encodes guanine nucleotide-binding protein α subunit (Gsα). The mutation sites of GNAS mutation in PMP are relatively stable, usually at Chr20: 57,484,420 (base pair: C-G) and Chr20: 57,484,421 (base pair: G-C). Typical GNAS mutation results in the reduction of GTP enzyme activity in Gsα, causing failure to hydrolyze GTP and release phosphoric acid, and eventually the continuous binding of GTP to Gsα. The activated Gsα could thus continuously promote mucin secretion through stimulating the cAMP-PKA signaling pathway, which is a possible mechanism leading to elevated mucin secretion in PMP. Conclusion GNAS mutation is one of the most important molecular biological features in PMP, with major functions to promote mucin hypersecretion.